Apnoea and bradycardia during epileptic seizures: relation to sudden death in epilepsy. Issue 3 (March 1996) - Nashef, L; Walker, F; Allen, P; Sander, J W; Shorvon, S D; Fish, D R
Abstract : OBJECTIVE--To record non-invasively ictal cardiorespiratory variables. METHODS--Techniques employed in polysomnography were used in patients with epilepsy undergoing EEG-video recording at a telemetry unit. RESULTS--Apnoea (> 10, range > 10-63, mean 24 s) was seen in 20 of 47 clinical seizures (three secondary generalised, 16 complex partial, and one tonic) and 10 of 17 patients. Apnoea was central in 10 patients, but obstructive apnoea was also recorded in three of 10. Oxyhaemoglobin saturation (SpO2) dropped to less than 85% in 10 seizures (six patients). An increase in heart rate was common (91% of seizures). Bradycardia/sinus arrest was documented in four patients (mean maximum RR interval 5.36, range 2.8-8.6 s) but always in the context of a change in respiratory pattern. CONCLUSION--Ictal apnoea was often seen. The occurrence of bradycardia in association with apnoea suggests the involvement of cardiorespiratory reflexes. Similar mechanisms may operate in cases of sudden death in epilepsy.